Association of Age of Metabolic Syndrome Onset With Cardiovascular Diseases: The Kailuan Study - Huang, Zegui; Wang, Xianxuan; Ding, Xiong; Cai, Zefeng; Li, Weijian; Chen, Zekai; Fang, Wei; Cai, Zhiwei; Lan, Yulong; Chen, Guanzhi; Wu, Weiqiang; Chen, Zhichao; et al. (Frontiers in Endocrinology, 2022)
Background Metabolic syndrome (MetS) is associated with an increased risk of incident cardiovascular diseases (CVD), but the association between the new-onset MetS at different ages and the CVD risk remain unclear. Methods This was a prospective study comprising a total of 72,986 participants without MetS and CVD who participated in the Kailuan study baseline survey (July 2006 to October 2007). All participants received the biennial follow-up visit until December 31, 2019. In addition, 26,411 patients with new-onset MetS were identified from follow-up, and one control participant was randomly selected for each of them as a match for age (±1 year) and sex. In the end, a total of 25,125 case-control pairs were involved. Moreover, the Cox proportional hazard model was established to calculate the hazard ratios (HR) for incident CVD across the onset age groups. Results According to the median follow-up for 8.47 years, 2,319 cases of incident CVD occurred. As MetS onset age increased, CVD hazards gradually decreased after adjusting for potential confounders. Compared with non-MetS controls, the HR and the 95% confidence interval (CI) for CVD were 1.84 (1.31–2.57) in the MetS onset age <45 years group, 1.67 (1.42–1.95) for the 45–54 years group, 1.36 (1.18–1.58) for the 55–64 years group, and 1.28 (1.10–1.50) for the ≥65 years group, respectively (p for interaction = 0.03). Conclusions The relative risks of CVD differed across MetS onset age groups, and the associations was more intense in the MetS onset group at a younger age.